2009
DOI: 10.1371/journal.pone.0004571
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Binding Sites Are Genetic Determinants of Retroviral Integration in the Human Genome

Abstract: Gamma-retroviruses and lentiviruses integrate non-randomly in mammalian genomes, with specific preferences for active chromatin, promoters and regulatory regions. Gene transfer vectors derived from gamma-retroviruses target at high frequency genes involved in the control of growth, development and differentiation of the target cell, and may induce insertional tumors or pre-neoplastic clonal expansions in patients treated by gene therapy. The gene expression program of the target cell is apparently instrumental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 54 publications
3
71
0
8
Order By: Relevance
“…10 Furthermore, contrary to HIV, MuLV demonstrated a strong preference for DNase I hypersensitive sites and regions rich in transcription factor binding site motifs. 17,18 Moreover, its bias appeared to be mostly determined by the MuLV-specific integrase 17,18 and the enhancer in the LTR. 17 HIV integrations associated with epigenetic marks such as H3K36me3, consistent with its reported bias for transcriptionally active genes.…”
Section: Chromatin Landscapes Of Integration Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Furthermore, contrary to HIV, MuLV demonstrated a strong preference for DNase I hypersensitive sites and regions rich in transcription factor binding site motifs. 17,18 Moreover, its bias appeared to be mostly determined by the MuLV-specific integrase 17,18 and the enhancer in the LTR. 17 HIV integrations associated with epigenetic marks such as H3K36me3, consistent with its reported bias for transcriptionally active genes.…”
Section: Chromatin Landscapes Of Integration Biasmentioning
confidence: 99%
“…17,18 Moreover, its bias appeared to be mostly determined by the MuLV-specific integrase 17,18 and the enhancer in the LTR. 17 HIV integrations associated with epigenetic marks such as H3K36me3, consistent with its reported bias for transcriptionally active genes. 19 These and other studies on retroviral integration biases were reviewed extensively in.…”
Section: Chromatin Landscapes Of Integration Biasmentioning
confidence: 99%
“…The retroviral propensity for frequently targeting oncogenes and cell growth/survival genes and the integration preference for TSSs and CpG islands synergistically increase the malignant potential of retroviral vectors (21). In addition, MLV considerably prefers transcription factor binding sites (TFBSs) (22) and moderately genes, especially highly expressed genes, during integration (16,21). Another gamma-retrovirus, porcine endogenous retrovirus (PERV), shows a similar integration pattern, favoring TSSs and CpG islands (23).…”
Section: Retroviral Integration Preferences For Genomic Regions Rich mentioning
confidence: 99%
“…In addition, HIV-1 targets oncogenes and the genes involved in cell growth and survival (21). In contrast, HIV-1 disfavors CpG islands and does not show any preference for TFBSs (16,22,26). Interestingly, integrated lentiviral vectors can both up-and down-regulate host gene expression, in contrast to MLV (20).…”
Section: Lentiviral Integration Into Actively Transcribed Genesmentioning
confidence: 99%
“…It has been suggested that interactions among retroviral pre-integration complexes (PICs) and cellular proteins, such as transcription factors (TFs), determine viral integration sites via a mechanism in which cellular proteins tether PICs to certain genomic loci (Engelman and Cherepanov, 2008;Felice et al, 2009). However, only a fraction of host proteins associating with retroviral PICs have been identified, and other mechanisms that underlie such interactions are still poorly understood (Cattoglio et al, 2010).…”
Section: Introductionmentioning
confidence: 99%